Policing the industrial reserve army: an international study - Rigakos, George S. (Crime, law and social change, 2011)
Over the past three decades, the industrialized world has witnessed four resilient social trends: (1) the consistent erosion of union-membership; (2) an increase in income polarization and inequality; (3) a dramatic resurgence in popular protest; and (4) a steady rise in public and private policing employment. In this paper, we examine the relationship between these trends by theorizing and operationalizing the notion of the "industrial reserve army" and a series of related tenets in order to conduct an international (N = 45), empirical test of a nascent Marxian model of policing. By treating total policing employment as an empirical barometer of bourgeois insecurity we find that this insecurity is conditioned by two elements of Marxian political economy: (1) relative deprivation (income inequality) and (2) the rise of an industrial reserve army (manufacturing employment and unemployment). Second, while surplus value and labour militancy (strikes and lockouts per 100,000 population) rise along with union membership, the presence of higher rates of unionization appears to ameliorate the need for more policing in all but post-USSR countries. While unions assist in checking the immiseration of workers through labour actions, union membership is nonetheless inversely correlated to policing employment, giving credence to the Marxian idea that while unions help mitigate against the exploitation workers, they also act as "lieutenants of capital," performing an essential policing function under capitalism.